The Design, Synthesis, and Biological Evaluation of Compounds with Medicinal Value - Sinicropi, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book explores issues concerning the design, synthetic methods and biological evaluation of molecules of pharmaceutical interest.